STRUCTURE, MORPHOLOGICAL, MAGNETIC AND OPTICAL PROPERTIES OF CuxMg1-xFe2O4 (x = 0, 0.5, 1) NANO FERRITES SYNTHESIZED BY CO-PRECIPITATION METHOD - Chinh (Journal of Military Science and Technology, 2021)
CuxMg1.xFe2O4 nanoparticles were successfully synthesized by co-precipitation. The samples were calcined at 900 oC for 3 h and X-ray diffraction analysis showed that Cu0.5Mg0.5Fe2O4 had a single phase cubic spinel structure, while formation of secondary phase of Fe2O3 was observed in XRD patterns of CuFe2O4, MgFe2O4. The saturation magnetization (Ms) of Cu0.5Mg0.5Fe2O4 is in between the saturation magnetization values of CuFe2O4 and MgFe2O4 nanoparticles, CuFe2O4 is a ferromagnetic material, while MgFe2O4 and Cu0.5Mg0.5Fe2O4 show superparamagnetic behavior. The synthesized spinel ferrites were fully characterized using scanning electron microscopy (SEM), FTIR spectroscopy, energy dispersive spectroscopy (EDS) and UV-vis spectrophotometry.